Selection of Wood Based on Acoustic Properties for the Solid Body of Electric Guitar - Anton ZORIČ; Jasmin KALJUN; Ervin ŽVEPLAN; Aleš STRAŽE (Archives of Acoustics)
For the purpose of making of a solid body of an electric guitar the acoustic- and mechanical properties of walnut- (Juglans regia L.) and ash wood (Fraxinus excelsior L.) were researched. The acoustic properties were determined in a flexural vibration response of laboratory conditioned wood elements of 430 × 186 × 42.8 mm used for making of a solid body of an electric guitar. The velocity of shear- and compression ultrasonic waves was additionally determined in parallel small oriented samples of 80 × 40 × 40 mm. The research confirmed better mechanical properties of ash wood, that is, the larger modulus of elasticity and shear modules in all anatomical directions and planes. The acoustic quality of ash wood was better only in the basic vibration mode. Walnut was, on the other hand, lighter and more homogenous and had lower acoustic- and mechanic anisotropy. Additionally, reduced damping of walnut at higher vibration modes is assumed to have a positive impact on the vibration response of future modelled and built solid bodies of electric guitars. When choosing walnut wood, better energy transfer is expected at a similar string playing frequency and a structure resonance of the electric guitar.